(untitled) (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2023)
One of the fish handling techniques needed to maintain fish freshness is the cold chain application. Cold chain system is very important to be applied in the post-catch handling process to extend the fish rigor mortis phase. Fishermen and fishmongers are people who play an important role in maintaining fish freshness. The purpose of this study was to determine the fresh sardine organoleptic quality after catching until reaching consumers or initial selling. The method used is a survey method through on board direct fish handling activity observation conducted by fishermen and fishmongers at selling locations, as well as fish organoleptic tests using score sheets for fresh fish with observations based on transit time starting from fishing vessel after catching, collectors, fishmongers to the first consumers. Organoleptic quality measurement of sardine taken from fishmongers in Atapupu waters showed that sardine quality fitted for consumption with an organoleptic value of >7.